The Poetics of Life: COVID-19, Improvising Alternatives, and the Musical Learning Community - Rubio Carrillo, Víctor Manuel; Argueta, Joshua; Lopez, Natalie Vanessa; Echeverría, David; Duque, Cristina; López, Sebastián (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
We are a group of musicians, artists, and educators who founded the Musical Learning Community within the Action Research Network of the Americas (ARNA). From Ecuador, Sebastián is a teaching artist working in a rural public conservatory in Amaguaña and David is a faculty member in a private university in Quito. Cristina is a dancer and educator working in Indonesia, while Víctor is an action researcher working from Miami. Natalie and Joshua are music educators in Miami-Dade County Public Schools. For the six of us, collaborating as an action research community has allowed our work to transcend our unique settings. In this article, through videos, testimonies, and collaborative analysis, we share our experiences in a way that resonates more like a chorus than the voice of a soloist.